Perceived sexual orientation based on vocal and facial stimuli is linked to self-rated sexual orientation in Czech men - Valentova, Jaroslava Varella; Havlíček, Jan (PloS one, 2013)
Previous research has shown that lay people can accurately assess male sexual orientation based on limited information, such as face, voice, or behavioral display. Gender-atypical traits are thought to serve as cues to sexual orientation. We investigated the presumed mechanisms of sexual orientation attribution using a standardized set of facial and vocal stimuli of Czech men. Both types of stimuli were rated for sexual orientation and masculinity-femininity by non-student heterosexual women and homosexual men. Our data showed that by evaluating vocal stimuli both women and homosexual men can judge sexual orientation of the target men in agreement with their self-reported sexual orientation. Nevertheless, only homosexual men accurately attributed sexual orientation of the two groups from facial images. Interestingly, facial images of homosexual targets were rated as more masculine than heterosexual targets. This indicates that attributions of sexual orientation are affected by stereotyped association between femininity and male homosexuality; however, reliance on such cues can lead to frequent misjudgments as was the case with the female raters. Although our study is based on a community sample recruited in a non-English speaking country, the results are generally consistent with the previous research and thus corroborate the validity of sexual orientation attributions.
Keywords: Homosexuality, Male; Humans; lidé středního věku; zpráva o sobě; Self Report; Stereotyping; obličej; Female; mladý dospělý; dospělí; lidé; hlas; sociální percepce; Adult; ženské pohlaví; Male; homosexualita mužská; Middle Aged; stereotypizace; Adolescent; Czech Republic; Voice; Homosexuality, Female; Young Adult; Face; Česká republika; mužské pohlaví; homosexualita ženská; Social Perception; mladiství